Research Progress on Feeding Behavior of Prawn Based on Passive Acoustics - Huang, Nanqing (International Journal of Public Health and Medical Research, 2024)
Passive acoustic monitoring (PAM) technology can obtain the sound information of aquatic organisms without causing disturbance or damage to aquatic organisms, and use the information for various ecological research and aquaculture activities management. With the continuous improvement and progress of prawn culture technology, the density of prawn culture continues to increase, but the problems such as low feed utilization rate and deteriorating water quality seriously restrict the rapid development of prawn culture. The use of passive acoustic monitoring technology can realize intelligent automatic feeding, improve feed utilization and alleviate water quality deterioration. This paper mainly describes the feeding process of prawn and its influencing factors, summarizes the research progress and application of passive acoustic monitoring technology in the acoustic signal of prawn feeding in recent years, analyzes the advantages and disadvantages of passive acoustic monitoring technology, and puts forward the future development trend in view of the existing problems, in order to provide a reference for the automatic feeding system to become intelligent.